Changing environmental conditions impact the phenotypic plasticity of Carex acuta and Glyceria maxima, two common wet grassland species - Edwards, Keith R.; Glocker, Bernhard; Mastný, Jiří; Picek, Tomáš (Frontiers in Plant Science, 2025)
IntroductionMaintenance of species coexistence is an important and on-going subject of plant ecology. Here, we aimed to determine how Carex acuta and Glyceria maxima, two common, co-occurring plant species in European wet grasslands, respond to changing environmental conditions and what these changes portend for coexistence of these two species. Such studies are important for predicting and modelling the effects of management and climate change on wet grassland plant species composition and for maintaining the ability of wet grasslands to provide their important ecosystem services including carbon sequestration and water purification. Based on past studies, we hypothesized that both species would be affected by hydrologic changes but that these effects would be modified by nutrient conditions with fertilization having a more positive impact on G. maxima. MethodsWe established a mesocosm to distinguish the effect of hydrology and nutrients on the biomass allocation patterns of these two species to determine how environmental conditions may impact the life history traits of these two species, which would influence their ability to co-exist. Plants were grown in pots from late May to early September 2019 and subjected to two nutrient and three water level treatments. Half of the plants were harvested in July while the other half were harvested in early September and their biomass allocation patterns calculated. Univariable and multivariable analyses were conducted to determine the effects of the environmental treatments on the measured parameters. In addition, we determined the phenotypic plasticity of the two species and whether these showed allometric relationships to plant size. Results and discussionC. acuta was affected more by hydrologic changes, growing better in dry and saturated conditions, while fertilization had a more positive effect on G. maxima. Both species were stressed when flooded, but C. acuta more so than G. maxima. Contrary to our predictions, C. acuta produced more ramets and was taller than G. maxima. Both species showed plastic responses to changing nutrient and water conditions, but only some were related to plant size. Our results indicate that C. acuta and G. maxima are more likely to co-exist in oligo- to mesotrophic wet grasslands with fluctuating water levels.